2022
DOI: 10.1332/204674321x16472778502561
|View full text |Cite
|
Sign up to set email alerts
|

A death in the family: experiences of dying and death in which everyday family practices are embedded and enacted

Abstract: ‘Family’ is an important concept in end-of-life care policy and practice but familial relationships are rarely considered, beyond a bio-medical framework and/or as a resource for informal care. Furthermore, bereavement and grief have largely come to be seen as the domain for psychiatry and psychology. I argue for an exploration of death, dying and bereavement as experiences within which everyday family practices are embedded and enacted. In doing so, I draw on experiences, in an English setting, relating to my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…At the same time, sociological approaches themselves have largely neglected the relevance of ‘family’ in the aftermath of death. Recent research has however shown the significance of ‘doing’ and ‘being’ ‘family’ at the end of life, in regard to the dying process itself (Almack, 2022; Almack et al, 2010; Borgstrom et al, 2019; Ellis, 2018; Hilário and Augusto, 2021) and the arranging and conducting of the funeral (Woodthorpe, 2017; Woodthorpe and Rumble, 2016). Beyond the funeral, Pearce and Komaromy (2021: 16–17) consider how family life is ‘done’ and made meaningful after a parental death; such issues may include the reconfiguration of roles and responsibilities, the construction or silencing of narratives of collective ‘family’ memories or loss of the very concept of ‘family’.…”
Section: ‘Family’ Sociology and The Aftermath Of Deathmentioning
confidence: 99%
“…At the same time, sociological approaches themselves have largely neglected the relevance of ‘family’ in the aftermath of death. Recent research has however shown the significance of ‘doing’ and ‘being’ ‘family’ at the end of life, in regard to the dying process itself (Almack, 2022; Almack et al, 2010; Borgstrom et al, 2019; Ellis, 2018; Hilário and Augusto, 2021) and the arranging and conducting of the funeral (Woodthorpe, 2017; Woodthorpe and Rumble, 2016). Beyond the funeral, Pearce and Komaromy (2021: 16–17) consider how family life is ‘done’ and made meaningful after a parental death; such issues may include the reconfiguration of roles and responsibilities, the construction or silencing of narratives of collective ‘family’ memories or loss of the very concept of ‘family’.…”
Section: ‘Family’ Sociology and The Aftermath Of Deathmentioning
confidence: 99%
“…(Borgstrom et al, 2019). A 'doing family' perspective demystifies and provides a nuanced understanding of how families experience the end of life (Almack, 2022).…”
Section: Family Perspective In Palliative Carementioning
confidence: 99%
“…But it seems that this particular 'family event' (Morgan, 1985) has not (yet) been theorised through family sociology (Almack and Woodthorpe, 2021). Some exceptions here include a focus on (children's) accounts of biographical disruption through family death (Jamieson and Highet, 2013), children's perspectives and biographies interwoven with family deaths (Davies, 2019), and the implications for family and family relationships after a death (Finch and Mason, 2000;Almack, 2022;Walter, 2020;Ribbens McCarthy et al, under review). Family sociology has so much to offer here through the lens of family practices, with many of David's theoretical concerns central to such a project: 'families and troubles are mutually implicated […] families are constituted through the ways in which they respond to and create problems […] family boundaries are created and recreated through the engagement of family members with troubles' (Morgan, 2019(Morgan, : 2227(Morgan, , 2229.…”
Section: Agency and Structure: The Personal As Politicalmentioning
confidence: 99%